A delayed onset of bowel activity after the start of conventional polyethylene glycol predicts inadequate colon cleansing before colonoscopy: A prospective observational study. Issue 2 (April 2016) - Papastergiou, Vasilios; Papasavvas, Stelios; Mathou, Nicoletta; Giannakopoulos, Athanasios; Evgenidi, Aikaterini; Karagiannis, John A; Paraskeva, Konstantina D
Background: Evaluation of factors correlating with the quality of bowel preparation (QBP) is critical to ensure high-quality colonoscopy. Objectives: We sought to determine whether the time interval between the start of conventional polyethylene glycol (PEG) ingestion and the onset of bowel activity is predictive of QBP. Methods: Consecutive adult outpatients attending colonoscopy were prospectively assessed. Data including demographics, medical history, time of starting/completion of PEG and time when bowel activity started were recorded. The QBP was assessed according to the Ottawa bowel preparation score (OBPS); inadequate QBP was OBPS ≥7. Results: A total of 171 patients (92 males, mean age: 60.5 years) complying with preparation instructions were included. The median OBPS was 5 (range: 1–13) and 57 (33.3%) had inadequate QBP. The median interval between the initiation of PEG and the onset of bowel activity was 60 min (range: 9–300 min). Patients ( n  = 52, 30.4%) with a delayed (>90 min) onset of bowel activity had poorer QBP ( p  = 0.0001). In multivariate analysis, male gender (OR: 2.38, p  = 0.03), the interval between the end of preparation and the start of colonoscopy (OR: 1.94, p  = 0.02) and time to onset of bowel activity >90 min (OR: 3.38, p  = 0.004) were predictive of inadequate QBP. Conclusion: The time interval between the initiation of PEG ingestion and the onset of bowel activity is predictive of the QBP. Our data support "on demand" intensification of bowel preparation in patients with a delayed onset of purgative response to PEG.